(untitled) (Journal of Pakistan Orthopaedic Association, 2015)
Objective: To determine outcome of minimal invasive dynamic hip screw procedure for fixation of stable intertrochanteric fractures of the femur. Methodology: A total of 40 patients with closed stable intertrochanteric femur fractures (AO type A1.1 to A2.1) were operated with MIDHS technique. Reduction of postoperative haemoglobin and haematocrit, pain score, theatre time, length of hospital stay, evidence of wound infection, hip screw position and tip apex distance were studied. Results: Of 40 patients, 22 (55%) were female and 18 (45%) were male. 14 (35%) had left hip while 26 (65%) had right hip involvement. Mean age at the time of surgery was 54.5 years. Based on AO classification: 12 had A1.1, 17 had A1.2 and 11 had A2.1. Mean reduction of post-operative hemoglobin was 1.2g/dl and haematocrit was 0.07. The mean post-operative pain score was 2.8 (using Visual Analogue Scale). The mean duration of surgery was 38.6 minutes and mean time to discharge from hospital after surgery was 4.3 days. We had no instances of postoperative haematoma or infection, malalignmnent of lag screws position of the operated limb in any of the patients. Conclusion: The MIDHS fixation of intertrochanteric fractures in our view is a surgical esthetic procedure; it involves minimal bleeding, less post-operative pain, shorter duration of surgery and length of hospital stay without sacrificing reduction, alignment, screw position and fixation stability. Additionally, the technique is performed using a standard dynamic hip screw set and requires no additional equipment.